Don't Overlook the Drain: Ruptured Venous Aneurysms in Intracranial Dural AVF - Agarwal, Ujjwal; Gupta, Vipul; Singla, Radhey Shyam; Parthasarathy, Rajsrinivas (Journal of Clinical Interventional Radiology ISVIR, 2025)
Venous aneurysms are typically regarded as secondary vascular anomalies arising from chronically elevated venous pressures and ectatic changes in draining veins, particularly in the setting of dural arteriovenous fistulas (dAVFs). Their presence is often associated with an increased risk of intracerebral hemorrhage. However, the occurrence of a discrete, saccular venous aneurysm resembling an arterial aneurysm—arising from a draining vein without angiographic evidence of venous hypertension or ectasia—is exceptionally rare and poorly characterized. We present an unusual case in which a patient presented with ruptured venous aneurysms in association with dAVFs lacking any evidence of venous outflow restriction or ectasia.
Keywords: venous aneurysm; ICH; embolization; dAVF